(untitled) (Research, Society and Development, 2020)
This study reports on workshops developed with students from the early years of elementary school, from a public school located in the municipality of Duque de Caxias, in the state of Rio de Janeiro. The objective was to explore the potential of music that would allow discussion and the construction of socio-scientific knowledge, in a playful and contextualized way. A participant research was carried out, involving students from the school. The theme of the workshops, “Washing hands”, was selected, considering the problems identified in the local reality marked by recurrent diseases. From the contextualization carried out by means of a song lyric, in the workshops, the involvement, the participation of the students, the stimulus to debate and questioning, as well as the development of critical sense was noticeable thus characterizing the assumptions of a teaching in Science, Technology and Society (STS).